Association of Thr715Pro P-Selectin Gene Polymorphism in Diabetic Retinopathy in North Indian Population: A Prospective Clinical Study - Sharma, Ritika; Kant, Shri; Mishra, Deepak; Srivastav, Tanmay; Singh, Hemendra (Nepalese Journal of Ophthalmology, 2021)
Introduction: The aim of this study was to evaluate the role of Thr715Pro P-Selectin gene polymorphism in patients with Diabetic Retinopathy in North Indian population and establish its role in the pathophysiology as an independent factor. Materials and methods: This is a prospective clinical study conducted on 60 patients at a tertiary care centre in North India over a period of eighteen months. Sixty patients satisfying the inclusion criteria were selected from the Vitreoretina clinic in the department. They were categorised equally in three groups namely Diabetics with diabetic retinopathy (DwDR), Diabetics without diabetic retinopathy (DwoDR), and non diabetics. The non-diabetics group was further divided into healthy controls, Hypertensive Retinopathy (HR) and Non-exudative Age Related Macular Degeneration (NEAMD). All the patients underwent complete ophthalmic evaluation and blood samples were drawn for the genetic study with their informed consent. Data was analysed using SPSS software version 16. Results: The genotypic analysis between DwDR, DwoDR and the three subgroup of controls comprising of healthy controls, HR and NEAMD showed that Thr715Pro (A/C) polymorphism prevalence was significantly high in DwDR (p = 0.003) and DwoDR (p = 0.003) compared to healthy controls. No significant difference was noted between DwDR, DwoDR and the HR and NEAMD groups. Conclusion: Thr715Pro P-Selectin gene Polymorphism could not be established as an independent factor in the pathogenesis of diabetic retinopathy, as its association is found with other systemic diseases which create a prothrombotic state.